Activity profiling of vacuolar processing enzymes reveals a role for VPE during oomycete infection. - Misas-Villamil, J; Toenges, G; Kolodziejek, I; Sadaghiani, A; Kaschani, F; Colby, T; Bogyo, M; van der Hoorn, R (2013)
Vacuolar processing enzymes (VPEs) are important cysteine proteases that are implicated in the maturation of seed storage proteins, and programmed cell death during plant-microbe interactions and development. Here, we introduce a specific, cell-permeable, activity-based probe for VPEs. This probe is highly specific for all four Arabidopsis VPEs, and labeling is activity-dependent, as illustrated by sensitivity for inhibitors, pH and reducing agents. We show that the probe can be used for in vivo imaging and displays multiple active isoforms of VPEs in various tissues and in both monocot and dicot plant species. Thus, VPE activity profiling is a robust, simple and powerful tool for plant research for a wide range of applications. Using VPE activity profiling, we discovered that VPE activity is increased during infection with the oomycete pathogen Hyaloperonospora arabidopsidis (Hpa). The enhanced VPE activity is host-derived and EDS1-independent. Sporulation of Hpa is reduced on vpe mutant plants, demonstrating a role for VPE during compatible interactions that is presumably independent of programmed cell death. Our data indicate that, as an obligate biotroph, Hpa takes advantage of increased VPE activity in the host, e.g. to mediate protein turnover and nutrient release.